MYTH AS A CONCEPT - Sukhodub , Tetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2024)
Introduction. The article examines myth as a transhistorical phenomenon of human existence in the aspect of its functions that are significant for modern times. The aim of the study is to analyze the phenomenon of myth in the context of its positive and negative impact on the sociocultural development of modern humanity. Research tasks are to analyze the features and basic principles of the mythological type of human consciousness; and show the expediency of considering myth as a concept of spiritual and sociocultural development in scientific discourse. The core of the research methodology is based on historical and philosophical, semiotic, scientific and systematic approaches, as well as cognitive and value settings of hermeneutics. Research results. In the current stage of the globalization process, there is an increasing role of myth as a phenomenon of specific thinking and language that contributes to the formation of a certain image of reality. In the spiritual and cultural aspect, myth serves as a connecting link between eras, traditions and modern cultures, which has a positive effect on the consciousness of modern human. Myth plays a negative role if it is considered as the only possible way of functioning of globalist relations. Discussion. The research emphasized: firstly, the investigation of mythology as the primordial type of human worldview self-awareness, alongside the persistence of "archaic" (mythological) elements in the sociocultural processes of contemporary society (P. Gurevich, M. Eliade, E. Canetti, O. Polysaev, E. Rezhabek, K. Hübner); secondly, the examination of scientific discourse on mythology within the context of its politicization and evolution into a social phenomenon (H. Ortega-y-Gasset, V. Reich, J. Sorel, N. Taleb, C. Flood, E. Fromm, F. Fukuyama and others); and thirdly, the exploration of the myth’s specificity and role in the current globalization process (L. Drotianko, J. Campbell, S. Ordenov, Yu. Pavlenko, M. Savelyeva, V. Fadeev, A. Vusatiuk and others). To grasp the concept of myth, works dedicated to defining the concept within modern philosophical and scientific discourse were consulted (A. Zalevskaya, S. Neretina, V. Ryzhko). Conclusions. The examination of modern civilization’s trajectory in the early 21st century, marked by globalism, reveals myth’s transhistorical nature of myth as a sociocultural phenomenon, a type of thinking and ideological self-awareness of a human. Cognitive indistinction between rational and irrational, natural and supernatural, meaning and sense, "I" and "we", etc. as structural elements of sensual and figurative mythological thinking, distorts our contemporary worldview, laying the groundwork for the manipulation of human consciousness. Viewing myth through the lens of "concept" frames it as an idea or scientific notion, as the "property" of an individual or social group. This perspective sheds light on myth’s impact on globalization, including its reinforcement, the emergence of global ideologies, and shifts in ethical understandings within global relations.